(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2021)
The theoretical essay aims to verify which factors influence teachers and researchers to adopt the measures guided by the International Financial Reporting Standards (IFRS) from a mimetic institutional perspective and instigate a critical position as to why this process is carried out with few questions. The adoption of international standards occurred through translations issued by the Accounting Pronouncements Committee (CPC), which brings a significant increase in the information disclosed, which does not necessarily represent an increase in the quality of the information. There are few studies that analyze the application of international norms and the participation of members of the academic area in Public Hearings on the CPC, therefore, the participation of these professionals in Public Hearings was observed, a period in which, after the international standard was translated, the community has to contribute suggestions. According to the analysis of the data available on the CPC website, there was a low participation in these hearings, which led to a verification of how educational institutions adapt to the accounting changes that occurred without analyzing their relevance to local standards, in order to offer contributions in the applicability and instigating researchers to a critical reading of published CPCs.